Investigation of Solubility Enhancement Approaches of Ticagrelor - A. Mohammed, Ihsan; M. Ghareeb, Mowafaq (Iraqi Journal of Pharmaceutical Sciences, 2018)
ABSTRACT Ticagrelor is an orally administered antiplatelet medicine, direct-acting P2Y12-receptor antagonist. Ticagrelor binds reversibly and noncompetitively to the P2Y12 receptor at a site distinct from that of the endogenous agonist adenosine diphosphate (ADP). Inhibition of platelet aggregation stimulated by ADP is a commonly used pharmacodynamic parameter for P2Y12-receptor antagonists. Ticagrelor is a crystalline powder with an aqueous solubility of approximately 10?g/mL at room temperature. Ticagrelor exhibits no pKa value within the physiological range. Ticagrelor does not exhibit pH-dependent solubility and is defined as ‘low solubility low permeability’ under the Biopharmaceutics Classification System (Class IV). The mean absolute bioavailability of ticagrelor in healthy volunteers is 36 % Nanoparticles preparation and complexation is one of the recently used approaches to enhance the solubility of drugs. The aim of the present work was to improve the solubility and dissolution of ticagrelor by preparing nanoparticles and cyclodextrin inclusion complex of ticagrelor and then incorporated in to tablet dosage form. Fifteen formulas of nanoparticles were prepared by antisolvent precipitation method (solvent displacement method) utilizing one of the three polymers (PVP, Poloxamer, and HPMC) at three different drugs: polymer and solvent: anti-solvent ratios and nine formulas of cyclodextrin inclusion complex with HP?CD by three preparation methods, physical trituration, kneading and solvent evaporation, which increase the solubility and dissolution rate of ticagrelor via formation of inclusion complex with HP?CD. The prepared formulas were characterized regarding the saturated solubility, polydispersity index, particle size by nano laser particle size analyzer, % yield, entrapment efficiency, and flowability, FTIR, DSC, and SEM. The selected formulas were prepared as tablets. The prepared tablets were evaluated for drug content, weight variation, hardness, and friability. In vitro dissolution data of the prepared tablets were analyzed using similarity factor (f2) and dissolution efficiency (DE). Among all the prepared nanoparticles formulas, formula (F12) which contain HPMC as a polymer at polymer: drug ratio of (1:1) and solvent: antisolvent ratio of (1:1) was considered as the optimum formula which shows good evaluation parameters in addition to the increment in the solubility to about 9 times than that of the pure drug. The nanoparticle of the selected formula (F12) incorporated tablets showed an acceptable tablet properties in addition to a considerable increase in the dissolution efficiency to (DE=92 % and 88 % in PH 1.2 and PH 6.8 respectively) in comparison to that of the marketed tablet (DE=89% and 85% in PH 1.2 and PH 6.8 respectively). Moreover, the analysis by DSC and SEM of the nanoparticles of the selected formula (F12) indicate a reduction in the crystallinity and amorphization of the drug. It can be concluded that the selected formula is a promising formula for the preparation of ticagrelor nanoparticles the incorporation in a tablet dosage form. Regarding ticagrelor inclusion complex with HP?CD Solvent evaporation method was the most effective method regarding ticagrelor solubilization and optimum formula of inclusion complex (F23) show increment in saturated solubility about ten times that of pure drug. The ticagrelor inclusion complex of the selected formula (F23) incorporated tablets showed an acceptable tablet properties in addition to a considerable increase in the dissolution efficiency to (DE=92 % and 90 % in PH 1.2 and PH 6.8 respectively) in comparison to that of the marketed tablet (DE=89% and 85% in PH 1.2 and PH 6.8 respectively).